Bioethics : an anthology - Kuhse, Helga; Singer, Peter (Blackwell Publishers, 1999)
This volume is a definitive, high-quality, one-volume collection of key primary texts for the study of bioethics. In its structure and content, the Anthology is intended to complement the Companion to Bioethics, edited by the same scholars. Drawing together the most important texts in the field, the volume will be of great value not only to philosophers, students of philosophy, and moral theologians, but also to doctors and nurses, sociologists and lawyers, and others working in health-care and biomedical sciences. Broadly based and of direct relevance to modern health-care dilemmas, Bioethics: An Anthology will also be of interest to the general reader.Equipped with an extensive index and covering all the relevant areas in bioethics, this volume provides an accessible overview of the subject matter and serves as a reference work, making a unique contribution to the field by collecting the key texts on such varied topics as the new genetics and reproductive technologies, euthanasia, AIDS, animal and human experimentation, nursing ethics and medical ethics, and the teaching and practice of bioethics.